The Non-Reading Reader: European Hebrew Literature at the Turn of the 20th Century - Netanʾel, Lilakh (Zutot, 2017)
European Hebrew literature presents a challenge to the study of early-twentieth-century national literature. By the end of the nineteenth century, the reading of modern Hebrew in Europe was neither part of a religious practice, nor did it merely satisfy a purely aesthetic inclination. It mainly functioned as an ideological means used by a minority of Jews to support the linguistic-national Jewish revival. However, some fundamental contradictions put into question the actual influence of this literature on the political sphere. This article asks a series of questions about this period in the history of Hebrew readership: How did the non-spoken Hebrew language come to produce popular Hebrew writings? How did this literature engage the common Jewish reader? In this article I propose a new consideration of Hebrew reading practices. I argue for the inclusion of the non-reading readers as important contributors to the constitution of the Jewish literary nation.